(untitled) (International Journal of Engineering and Computer Science, 2016)
MANET and VANET are the active research areas and lots of routing protocols have been proposed for use in these areas.. In MANET, nodes are connected through wireless channels in a network and each node acts as a router and as a host. One of the scenario of MANET is Vehicular ad-hoc networks. For communication in VANET, efficient Routing Protocols are needed. Because of highly changing network topology and frequent disconnection it’s strenuous to design an efficient routing protocol for vehicles, there can be two types of VANET that are V2V(Vehicle to Vehicle) and V2RSU(Vehicle to Road Side Unit). Because of daily happening of accidents VANET is one of the affecting areas for the refinement of Intelligent Transportation System (ITS) which can insure passengers and road safety. The Intelligent Transport Systems gives information if there exists any emergency and tells about traffic density. the traffic and traffic density. The existing routing protocols for VANET are not efficient enough to meet all traffic scenarios. Worthy routing protocols are required to initiate communication between vehicles in future for passengers and road safety. This paper shows literature survey related to Reactive and Proactive Routing Protocols of MANET as AODV, DSDV, OLSR, and DSR. Analysis and characterization of these protocols is shown in the paper which helps in further improvement of existing routing protocols.